Molecular characterization of pigeon torque teno virus (PTTV) in Jiangsu province. (August 2017) - Zhang, Zhicheng; Dai, Wei; Dai, Dingzhen
Graphical abstract: The torque teno virus (TTV) is a recently discovered DNA virus that has been detected in many different hosts, including humans, livestock and poultry. In this study we employed PCR to detect pigeon TTV (PTTV) in 144 samples collected from 6 pigeon plants in Jiangsu province, amplify complete genomes from representative samples and analyze genetic characteristics using bioinformatics. The rate of sequence homology among the six PTTV complete genomes obtained from Jiangsu province ranged from 99.7% to 100%. Phylogenetic analysis suggested that the PTTV genomes had a high degree of genetic similarity and were similar to chicken anemia virus that also had poultry as a host. Although with the same host, PTTV shared distant relationship with PiCV in both complete genome, Rep and Cap genes. The results of this study provided evidence that PTTV could be detected in Chinese pigeons at a high level, the evolutionary process of complete genome, Rep and Cap genes of Anelloviridae family had obvious divergence. Highlights: PTTV was detected in 71.5% of 144 pigeon samples. The rate of sequence homology among 6 PTTV complete genomes was from 99.7% to 100%. PTTV strains had a very close genetic relationship and sequence identity to CAV in complete and Cap phylogenetic tree. Abstract: The torque teno virus (TTV) is a recently discovered DNA virus that has been detected in many different hosts, including humans, livestock and poultry. To date, there is no report of pigeon TTV (PTTV) from anywhere in the world. To investigate the distribution of PTTV in pigeons from the eastern Chinese province of Jiangsu and characterize their genomes, we employed PCR to detect PTTV in 144 samples collected from 6 pigeon plants in Jiangsu province, amplify complete genomes from representative samples and analyze genetic characteristics using bioinformatics. The results demonstrated that 71.5% (103/144) of samples were PTTV positive. The rate of sequence homology among the six PTTV complete genomes obtained from Jiangsu province ranged from 99.7% to 100%. Phylogenetic analysis suggested that PTTV genomes had a high degree of genetic similarity and were similar to chicken anemia virus that also had poultry as a host. Although with the same host, PTTV shared distant relationship with PiCV in both complete genome, Rep and Cap genes. The results of this study provided evidence that PTTV could be detected in Chinese pigeons at a high level, the evolutionary process of complete genome, Rep and Cap genes of Anelloviridae family had obvious divergence.